The effect of entrepreneurship education, income expectations and family environment on entrepreneurial interest based on gender - Fajar Anggraini; Diah Pranitasari (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2025)
This study examines the effects of entrepreneurship education, income expectations, and family environment on students' entrepreneurial interest at a private college in Jakarta. A quantitative approach was employed, with data collected through a questionnaire distributed via Google Forms. The population comprised students from the 2020, 2021, and 2022 cohorts at the same institution who had completed entrepreneurship courses. A sample of 100 respondents was analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS version 4.1.0.1. The findings indicate that entrepreneurship education has a direct positive effect on entrepreneurial interest, while income expectations show no significant effect. In contrast, the family environment demonstrates a direct effect on entrepreneurial interest. From a practical standpoint, higher education institutions should strengthen experiential entrepreneurship curricula and foster supportive family engagement through workshops or parent outreach programs. Policymakers may consider integrating family-based entrepreneurial mentoring into formal education. Educators should not overemphasize income expectations when promoting entrepreneurship, as financial motives alone do not significantly drive student interest.